2016
DOI: 10.12700/aph.13.7.2016.7.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Nano-structured Surface Layer on Titanium Implants for Osteoblast Proliferation Activity

Abstract: The goal of this study is to compare surface morphologies on dental implants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…Subsequently, different surface treatments have been given greater importance in the long-term success of implants. The interaction of proteins at the nanometric level is emerging as a crucial factor for the integration of implants [ 28 , 29 ]. Nevertheless, recent studies have shown that with various surface treatments, different osseointegration periods can be achieved [ 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, different surface treatments have been given greater importance in the long-term success of implants. The interaction of proteins at the nanometric level is emerging as a crucial factor for the integration of implants [ 28 , 29 ]. Nevertheless, recent studies have shown that with various surface treatments, different osseointegration periods can be achieved [ 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A lágyrész-és keményszöveti augmentáció, valamint a protetikai fej megfelelő kialakítása a hosszú távú stabil kapcsolat létrehozására törekszik. Szóba jöhet az implantátum aktív felszínének tisztítását célzó kezelés is, ha az említett felület kapcsolatba került a szájüreggel és annak flórájával [8,9,15]. Az implantátum eltávolítása mindig csontveszteséggel jár, ami az újraimplantálás lehetőségét nehezíti.…”
Section: Megbeszélésunclassified
“…Following a six-month healing period, a 2.9 mm diameter sandblasted, large-grit, acid-etched implant was placed without any further augmentation [20][21][22] (Figure S1). Bilayer tunnel approach for guided bone regeneration (Case #1).…”
Section: Radiographic Image Acquisitionmentioning
confidence: 99%